2018
DOI: 10.2147/ndt.s182423
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in patients treated with electroconvulsive therapy

Abstract: BackgroundElectroconvulsive therapy (ECT) is an effective treatment method for severe mental illnesses. ECT has gone through significant modernization. Side effects of ECT have largely decreased. Temporary disturbance of cognitive performance can be still present as a side effect of electroconvulsive treatment.MethodsCognitive functioning in the sample of patients with severe and acute mental illness treated with electroconvulsive therapy (ECT) was assessed. Basic assessment of cognitive functions was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…In a recent case-control study on ECT in acute mental illness, where the mean age of the sample was 50 years, improvement in cognitive functioning was observed. 63 Another study also reported improvement in cognitive aspects with ECT in treatment-resistant depression in older adults. 64 Overall, ECT in older adults for depression may have a more positive effect on cognition though it is known to cause transient acute cognitive deficits.…”
Section: Antidepressants Electroconvulsive Therapy and Cognitive Deficitsmentioning
confidence: 97%
“…In a recent case-control study on ECT in acute mental illness, where the mean age of the sample was 50 years, improvement in cognitive functioning was observed. 63 Another study also reported improvement in cognitive aspects with ECT in treatment-resistant depression in older adults. 64 Overall, ECT in older adults for depression may have a more positive effect on cognition though it is known to cause transient acute cognitive deficits.…”
Section: Antidepressants Electroconvulsive Therapy and Cognitive Deficitsmentioning
confidence: 97%
“…In addition, long-term short-term memory impairment has been reported in some patients who underwent ECT. 79 Finally, there are still no evidence-based safety recommendations for DBS, 62 although the procedure involves all the risks inherent to a neurosurgical procedure. 80 …”
Section: Discussionmentioning
confidence: 99%
“…Prawie 30% pacjentów wykazywało zaburzenia poznawcze po tygodniu od EW, jednocześnie po trzech miesiącach notowano dużą poprawę w tym zakresie [40]. Wynik badania Kalisovej [41] opublikowanego w 2018 roku również wykazał, że wielu pacjentów poddawanych EW ma deficyty w zakresie funkcji poznawczych wynikające z choroby podstawowej. Podkreślono, że mimo pogorszenia ich bezpośrednio po EW, to dzięki terapeutycznemu działaniu samego zabiegu, po kilku tygodniach wracają one do sprawności wyjściowej, a w dalszym okresie ulegają poprawie.…”
Section: Czy Choroba Podstawowa Ma Znaczenie?unclassified